Exploring the Pharmacological Mechanism of the Effective Chinese Medicines Against Gynecological Cancer Based on Meta-Analysis Combined With Network Pharmacology Analysis - Ren, Ning; Yu, Lulin; Qian, Lihui; Ye, Gewei; Zhu, Zhenzheng; Yu, Jieru; Sun, Leitao; Zhang, Leyin (Frontiers in Oncology, 2022)
This meta-analysis plus network pharmacology aimed to investigate whether TCM combined with chemotherapy is associated with more beneficial efficacy data in the treatment of gynecological cancer (GC). A total of 11 RCTs consisting of 863 GC patients were finally included. Results showed a better ORR (RR: 1.42, 95% CI: 1.18-1.71, P = 0.000), DCR (RR: 1.20, 95% CI: 1.07-1.35, P = 0.001), PD (RR: 0.27, 95% CI: 0.11-0.65, P = 0.003; I2 = 0.0%, P = 0.930), and QOL (SMD: 0.85, 95% CI: 0.38-1.33, P = 0.005); higher proportions of CD3+ T (WMD: 5.65, 95% CI: 4.23-7.08, P = 0.000; I2 = 68.3%, P = 0.004), CD4+ T (WMD: 6.97, 95% CI: 5.35-8.59, P = 0.000; I2 = 83.4%, P = 0.000) and ratio of CD4+/CD8+ T (WMD: 0.32, 95% CI: 0.23-0.42, P = 0.000; I2 = 78.0%, P= 0.000). The number of AEs was significantly lower in TCM + chemotherapy group. The active components and targets of 19 high-frequency Chinese medicines got from meta-analysis were screened and explored in network pharmacology analysis. And a regulatory network of active components and targets, core network and key genes, diagram of protein interaction, network topology analysis, and gene body GO function and KEGG pathway enrichment analysis was performed. 120 active components were identified. NPM1 and HSPA8 are the most critical target proteins in the core network of protein interaction. HSP90AA1 is the most important target protein in TCM group. KEGG enrichment analysis showed that it was highly significant in lipid and atherosclerotic pathways. Therefore, moderate evidence revealed that TCM plus chemotherapy has obvious advantages over chemotherapy alone in terms of tumor responses, QOL, peripheral blood lymphocyte levels, and fewer AEs in the treatment of GC. The potential important targets and core genes were displayed.